Effect of Sr Element Content on the Microstructure and Corrosion Resistance of Zn-2%Al-1.2%Mg Coating - LIN Wenjun, OUYANG Zhiyun, ZHAN Yangfang, MIAO Hualei, LIU Yang, ZHU Daibo (Cailiao Baohu, 2024)
In order to further investigate the regulation of trace alloying elements on the microstructure of coatings and the mechanism of their influence on corrosion resistance， a dual plating method was used to prepare Zn-2.0%Al-1.2%Mg-x%Sr (x ＝0， 0.03%， 0.06%， 0.09%，0.12%， mass fraction) coatings on Q235 steel plates.The effects of Sr element content on the microstructure and corrosion resistance of Zn-2.0%Al-1.2%Mg coatings were examined through scanning electron microscopy (SEM)， X - ray diffraction (XRD) and 5%NaCl immersion test.Results showed that adding an appropriate amount of Sr element could effectively refine the primary η-Zn phase in the solidification microstructure of the surface of Zn-2.0%Al-1.2%Mg coating， promoted the formation of a Zn/Al/MgZn2 ternary eutectic structure， and made the FeAl3-Znx columnar crystals in the intermediate alloy layer denser.Notably， when the addition amount of Sr was 0.09%， the refinement effect of solidification structure on the surface of the coating was most obvious， and the intermediate alloy layer was the thinnest and densest， at which time the coating had the lowest rate of immersion corrosion and the best corrosion resistance.